2018
DOI: 10.3390/md16090316
|View full text |Cite
|
Sign up to set email alerts
|

(+)-Aeroplysinin-1 Modulates the Redox Balance of Endothelial Cells

Abstract: The bioactive natural compound from marine origin, (+)-aeroplysinin-1, has been shown to exhibit potent anti-inflammatory and anti-angiogenic effects. The aim of the present study was to identify new targets for (+)-aeroplysinin-1 in endothelial cells. The sequential use of 2D-electrophoresis and MALDI-TOF-TOF/MS allowed us to identify several differentially expressed proteins. Four of these proteins were involved in redox processes and were validated by Western blot. The effects of (+)-aeroplysinin-1 were fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…The generation of ROS is mainly derived from complexes I and III of the mitochondrial electron transport chain or from the nicotinamide adenine dinucleotide phosphate NADPH oxidase family on the membrane, which affects the membrane permeability, resulting in mitochondria-mediated apoptosis [ 59 , 60 ]. Previous studies observed that Apl-1 could inhibit the peroxidase NADPH oxidase and activate superoxide dismutase (SOD) to regulate the oxidative balance of endothelial cells, but it did not affect the catalase activity [ 61 ]. To understand whether Apl-1 affects the oxidative balance of leukemia and prostate cancer cells, flow cytometry dye dihydroethidium (DHE) was used to evaluate reactive oxygen species generation in cancer cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The generation of ROS is mainly derived from complexes I and III of the mitochondrial electron transport chain or from the nicotinamide adenine dinucleotide phosphate NADPH oxidase family on the membrane, which affects the membrane permeability, resulting in mitochondria-mediated apoptosis [ 59 , 60 ]. Previous studies observed that Apl-1 could inhibit the peroxidase NADPH oxidase and activate superoxide dismutase (SOD) to regulate the oxidative balance of endothelial cells, but it did not affect the catalase activity [ 61 ]. To understand whether Apl-1 affects the oxidative balance of leukemia and prostate cancer cells, flow cytometry dye dihydroethidium (DHE) was used to evaluate reactive oxygen species generation in cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, previous reports showed that Apl-1 (20 μM) reduced the ROS content in RF-24 endothelial cells [ 61 ]. In this study, it was found that Apl-1 increased the accumulation of ROS in prostate cancer and leukemia cells ( Figure 4 a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, factors secreted by immune cells can increase mutation rates in cancer cells, thus enabling cancer cells to take on characteristics of other hallmarks (Grivennikov et al, 2010). Aeroplysinin-1 has the potential to inhibit inflammation by decreasing the levels of total reactive oxygen species (Garcia-Vilas et al, 2018), which may make this compound a promising agent to reduce the tumor-promoting effects of inflammation.…”
Section: Tumor-promoting Inflammationmentioning
confidence: 99%
“…Peroxyredoxin 2 (Prdx2) helps in the formation of vascular patterns in colon cancer cells HCT116 by vascular mimicry through the activation of VEGFR2, which is suppressed when siPrdx2 is used [116]. On the other hand, endothelial cells treated with the anti-angiogenic compound (+)-aeroplysinin-1 have increased protein levels of Prdx4 [114].…”
Section: Glutaredoxin and Peroxyredoxinmentioning
confidence: 99%